Edukasi Pemeriksaan Payudara Sendiri Berpengaruh terhadap Keterampilan Sadari Remaja Putri Usia 13-15 Tahun - Poppy Farasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The cause of high early death rates for women is caused by breast cancer, and is in second place in the world with new cases of 1.67. million. Early detection of signs and symptoms of breast cancer can be done independently by doing breast self-examination (BSE). Education about BSE is an alternative way to improve breast cancer prevention skills. This study aims to determine the effect of providing BSE education on BSE skills in young women aged 13-15 years (In Gesikan Pakel Village, Tulungagung 2022). The research design is a one group pre post test design with a quantitative approach. The population is all young women aged 13-15 years as many as 92 people with a purposive sampling technique obtained a sample of 35 respondents. The independent variable is breast self-examination education and the dependent variable is BSE skills. Data collection uses a BSE skills questionnaire sheet, then the data is processed through coding, scoring and tabulating. Statistical test using the Wilcoxon Signed Rank Test. The results showed that there was an increase in the skills of the respondents, namely before the treatment there were 20 respondents (57.1%) who had initial category skills, and after the treatment there were 18 respondents (51.4%) who had advanced category skills. The p value obtained is 0.000 and Î± is 0.05 which means the p value <Î± means that H0 is rejected and H1 is accepted. It was concluded that there was an effect of providing BSE education on BSE skills in young women aged 13-15 years in Gesikan Village. The success of providing education through demonstrations to school-age adolescents is able to increase concentration and skills in performing breast examinations. Thus the methods and techniques of BSE education can be improved for the success of BSE.